SOCIALIZATION OF TRI DHARMA MONITORING INSTRUMENTS HIGHER EDUCATION FOR STUDY PROGRAMS IN THE FKIP ENVIRONMENT OF TANJUNGPURA UNIVERSITY - Firmansyah, Haris; Riyanti, Dwi; Ariyati, Eka; Nurdini M., Asriah; Bunau, Eusabinus; Yunitaningrum, Wiwik; Pranata, Rio; Sahidi, Sahidi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The Community Partnership Program (PKM) aims to increase the understanding of study programs at the Faculty of Teacher Training and Education (FKIP) Tanjungpura University regarding the implementation and monitoring of the Tri Dharma of Higher Education, which includes education, research, and community service. This activity involves the socialization of monitoring instruments designed by the Faculty Quality Assurance Unit (UPMF) to evaluate the quality of academic and managerial services within FKIP. The approach used in this PKM includes socialization and Focus Group Discussion (FGD) which allows participants to provide input related to the instruments that have been socialized. The results of the PKM showed that the participants, consisting of the Head of Department, Head of Study Program, and representatives of the Quality Assurance Group, gained an in-depth understanding of the importance of monitoring and evaluation to ensure the quality of the Tri Dharma. Feedback from the FGD is also used to improve the monitoring instrument to be more relevant to the context of the study program. With effective monitoring instruments, it is hoped that the study program at FKIP Tanjungpura University can improve the quality of education, research, and community service according to the set standards, support the improvement of the quality of higher education, and make a positive contribution to the community.